The Diagnostic Accuracy of Parkinson's Disease Mild Cognitive Impairment Battery Using the Movement Disorder Society Task Force Criteria - Bezdicek, Ondrej; Nikolai, Tomas; Michalec, Jiri; Růžička, Filip; Havránková, Petra; Roth, Jan; Jech, Robert; Růžička, Evžen (Movement disorders clinical practice, 2017)
BACKGROUND: The aim of the present study was to provide empirical evidence regarding the classification accuracy of the International Parkinson and Movement Disorder Society (MDS) neuropsychological battery (NB) in the determination of Parkinson's disease mild cognitive impairment (PD-MCI). METHODS: The present cross-sectional study included 106 PD patients subjected to PD-MCI classification at Level I and 120 healthy controls (HCs). All HC and PD subjects were then assessed with MDS-NB at Level II and matched according to age and education using different thresholds (1.5 and 2.0 standard deviations [SDs] below average). RESULTS: We found that Level I and II resulted in different classifications of PD-MCI status. Detection thresholds of -1.5 SD and -2.0 SDs at Level II had also a significant impact on the discriminative validity of all measures in the MDS neuropsychological battery, based on area under the curve analyses. Overall, semantic fluency showed the highest potential in all comparisons not only between PD-MCI and HC, but also between PD-MCI and PD with no deficit (PD-ND). CONCLUSIONS: Our results show that the battery at Level II is applicable and that some measures, such as semantic fluency, have high discriminative validity in the detection of PD-MCI versus PD-ND and HCs.
Keywords: mild cognitive impairment; validity; Parkinson's disease